F FENOMENA CYBERBULLYING SEBAGAI MANIFESTASI PATOLOGI SOSIAL PADA AKUN INSTAGRAM @ABIDZAR73 - Yuafi, Hamdan (Sisi Lain Realita Another Side Of Reality Journal Criminology, 2025)
This research discusses the phenomenon of cyberbullying as a form of social pathology in digital society with a case study on the Instagram account @abidzar73. The development of technology and social media has changed the way people communicate, but it has also led to various behavioral deviations, one of which is cyberbullying. The purpose of this study is to identify the forms of cyberbullying that appear in Abidzar's Instagram comment section and analyze them as symptoms of social pathology using Émile Durkheim's theory. This research uses a descriptive qualitative approach with case study and netnography methods. Data were collected through documentation of 1,000 comments from Abidzar's uploads, which were then analyzed based on sentiment and thematic categories. The results show that negative comments containing insults, body shaming, and moral shaming against Abidzar are a clear form of weak social control and fading moral values in the digital space. Cyberbullying in this context not only has a psychological impact on individuals, but also reflects the dysfunction of values and norms in digital society.